Pengaruh Lingkungan Kerja Dan Motivasi Kerja Melalui Disiplin Kerja Terhadap Kinerja Karyawan Pada The Kirana Hotel Canggu, Badung - Surya Nugraha; Dewa Ayu Suryawati; Ni Putu Widhya Pibriari (Journal Research of Management, 2025)
Research objectives 1) To analyze the influence of the employee work environment on employee work 2) To analyze the influence of the work environment on employee work performance 3)To analyze the influence of employee work motivation on employee work discipline 4) To analyze the influence of work motivation on employee work performance 5) To analyze the influence of employee work discipline on employee work 6)To analyze the influence of the Employee Work Environment on Employee Work Performance through Employee Work Discipline.7)  To analyze the influence of employee work motivation on employee work performance.   The location of the research was conducted on employees at The Kirana Hotel Canggu, Badung.as many as 60 samples with a proportional random sampling technique using path analysis.